On the Eigenvalue Problem for One-Dimensional Differential Operator with Nonlocal Integral Condition - Čiupaila, R.; Jesevičiūtė, Ž.; Sapagovas, M. (Nonlinear Analysis: Modelling and Control, 2004)
The article investigates the eigenvalue problem for ordinary onedimensional differential operator with nonlocal integral condition. Such a problem is met in the literature quite rarely and is considerably less investigated. Also the conditions for existence of non-positive eigenvalue or multiple eigenvalues are obtained.